INFLUENCE OF INTRAUTERINE HYPOXIA TO THE FORMATION OF RAT’s VENTRICULAR CARDIO-MYOCYTES MITOCHONDRIAL COMPLEX DURING FIRST WEEK OF POSTNATAL ONTOGENESIS - Ivanchenko, M.V. (World of Medicine and Biology, 2014)
We studied a quantitative ultrastructural analysis of the reactions of mitochondria network in rat’s cardiomyocytes on the 1th, 3th, 7thdays of postnatal ontogenesis under previous influence of chronic intrauterine hypoxia. It was shown that fetal hypoxia leads to progressive changes of mitochondria during the first week of postnatal ontogenesis in rats. The primary alterations which associated with the direct influence of intrauterine hypoxia were attached to the secondary alterations in which posthypoxic state and oxidative stress lead to the persistence of the pathological process. Mitochondrion is characterized by pronounced degradations of subsarcolemmal organelles, swelling of «high-energy» interfibrillar mitochondria and alterations of «low-energy» paranuclear mitochondria, decrease in the number of associations between mitochondria.